Co-occurrence of occupational outcomes and associated factors among hospitals cleaners, eastern ethiopia: a cross sectional study - Sina Temesgen Tolera; Nega Assefa; Tesfaye Gobena; Abraham Geremew (BMC, 2024)
Abstract Background Hospital cleaners face a complex and varied work environment due to several potentially dangerous circumstances, including the risk of getting injured by sharp objects and being subjected to various ergonomic and physical risks. They thus acquire a combination or co-occurrence of outcomes associated to their line of work. In this study it stands for occurrence of occupational injuries and musculoskeletal disorders (MSDs) during study period, which has not been explored in developing countries like Ethiopia, particularly among hospital cleaners. Objective To assess the prevalence of co-occurrence of occupational outcomes and associated factors among hospital cleaners, Eastern Ethiopia. Methods A cross sectional study was conducted on 741 cleaners in eight hospitals in eastern Ethiopia from May, 2023 to 30th August, 2023. Face-to-face interview was conducted. The data quality was maintained by designing standard questions that preserved both external and internal validity. The entered data was exported from Epi-Data 3.1 to Stata 17MP. Descriptive statistic was used to characterize one variable, While, binary logistic regression was used to explore the relationship of the predictors. At binary analysis variables having a p-value of < 0.20 were candidates for multivariate logistic regression. The crude odds ratio and adjusted odds ratio (AOR) with a 95% confidence interval (CI) were presented. Those variables having < 0.05 were reported. The variance inflation factor used to test multicollinearity. While, Hosmer-Lemeshow goodness-of-fit-test was applied for model fit. Result From total of 741 hospital cleaners, 679 (91.63%) of them were responded. The prevalence co-occurrence of occupational outcome among cleaners was 25.04% (95%CI: 21.82, 28.47). The multivariate logistic regression shows that those had workload (AOR:2.78, 95%CI: 1.25,6.17), those worked more than 8r/day (AOR:3.45, 95%CI:2.34,6.32), those have sleeping disorders (AOR: 4.61,95%CI: 2.89, 8.03), those had work stress (AOR:2.05, 95%CI:0.98,4.29), those highly exposed with hazards (AOR: 4.22, 95%CI:2.40, 7.45) and those had poor knowledge of risk (AOR:2.41, 95%CI:1.06, 5.50) were more likely increase the odds of co-occurrence of occupational outcome as compared to their counterparts. Conclusion The current study concluded that one-fourth of the co-occurrence of occupational outcomes was reported among hospital cleaners. The study also found that lack of supervision, workload, working more hours per a day, severely presence of occupational hazards, lack of regular job rotation, the sleeping disorders and having work stress all increased the odds of co-occurrence occupational outcome. Graphical Abstract